Direct Evidence for Fluid Pressure, Dilatancy, and Compaction Affecting Slip in Isolated Faults. Issue 16 (12th August 2020) - Proctor, B.; Lockner, D. A.; Kilgore, B. D.; Mitchell, T. M.; Beeler, N. M.
Abstract: Earthquake instability occurs as a result of strength loss during sliding on a fault. It has been known for over 50 years that fault compaction or dilatancy may cause significant weakening or strengthening by dramatically changing the fluid pressure trapped in faults. Despite this fundamental importance, we have no real understanding of the exact conditions that lead to compaction or dilation during nucleation or rupture. To date, no direct measurements of pore pressure changes during slip in hydraulically isolated faults have been reported. We show direct examples of fluid pressure variations during nucleation and rupture using a miniature pressure transducer embedded in an experimental fault. We demonstrate that fluids not only are significant in controlling fault behavior but can provide the dominant mechanism controlling fault stability. The effect of fluid pressure changes can exceed frictional variations predicted by rate‐ and state‐dependent friction laws, exerting fundamental controls on earthquake rupture initiation. Key Points: Direct measurements of pore pressure show variations during nucleation and rupture using a miniature pressure transducer Fluids and intrinsic friction interact in controlling fault stability The effect of fluid pressure changes can exceed frictional variations predicted by the rate‐ and state‐dependent friction laws